Molecular Changes in the Adipose Tissue Induced by Rheumatoid Arthritis: Effects of Disease-Modifying Anti-Rheumatic Drugs - Arias de la Rosa, Iván; Escudero-Contreras, Alejandro; Ruiz-Ponce, Miriam; Román-Rodríguez, Cristóbal; Pérez-Sánchez, Carlos; Ábalos-Aguilera, María del Carmen; Ortega-Castro, Rafaela; Alcaide, Juan; Murri, Mora; Font, Pilar; Calvo-Gutiérrez, Jerusalem; Luque-Tevar, Maria; et al. (Frontiers in Immunology, 2021)
Disease severity, progression and response to therapy might be worse in obese rheumatoid arthritis (RA) patients, but paradoxically, obesity also might protect from radiographic joint damage. Thus, the intricate relationship between obesity and RA needs urgent clarification. The aim of this study was to assess the influence of obesity on the onset and development of RA, and to determine whether arthritis could modify the adipose tissue biology and whether conventional Disease Modifying Anti-Rheumatic Drugs (DMARDs) can modulate these alterations. Two strategies were followed: (1) clinical profiling of two cohorts of RA: non-obese and obese patients and (2) mechanistic studies carried out in both a collagen-induced arthritis (CIA) in an obese mouse model and 3T3-L1 adipocytes treated with cDMARDs (leflunomide, methotrexate and hydroxychloroquine). In our cohort of RA patients with low-moderate disease activity, the presence of obesity was not related to a higher activity of the disease, actually DAS28-ERS was reduced in the obese RA patients. However, the induction of arthritis aggravated the transcriptomic changes induced in the adipose tissue by obesity, modulating genes involved in inflammation, macrophage accumulation and M1 polarization state, adipogenesis and lipolysis. Treatment with hydroxychloroquine reduced weight and insulin resistance, accompanied by beneficial metabolic effects in the adipose tissue. These molecular changes in adipose tissue were also observed after methotrexate administration. In sum, arthritis might affect directly the inflammatory burden and metabolic alterations associated with obesity in adipose tissue. Clinicians should be cautious measuring the activity of the disease in obesity and managing the best therapeutic options for the metabolic comorbidities of these patients, where the combination of hydroxychloroquine and methotrexate should be considered to improve adipose tissue dysfunction in RA patients with obesity.